2017
DOI: 10.3126/ajms.v8i5.17136
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine levels in patients with Psoriasis

Abstract: Background: Hyper homocysteinaemia represents an independent risk factor for atherosclerotic cardiovascular disease, stroke, peripheral arterial occlusive disease and venous thrombosis. Psoriasis is a chronic inflammatory skin disease associated with increased atherothrombosis and cardiovascular risk profile. Aims and Objective: The aim of this study is to investigate homocysteine in psoriatic patients and its relationship with the severity of the disease.Materials and Methods: A case control study in 50 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…The majority of the studies in the literature demonstrated that patients with psoriasis have plasma/serum Hcy levels significantly higher than controls [8–18]. Among them, some reported that the severity of psoriasis assessed according to psoriasis area and severity index (PASI) directly correlate with plasma/serum Hcy levels [10,15,17,18].…”
Section: Hcy Levels In Patients With Psoriasismentioning
confidence: 99%
“…The majority of the studies in the literature demonstrated that patients with psoriasis have plasma/serum Hcy levels significantly higher than controls [8–18]. Among them, some reported that the severity of psoriasis assessed according to psoriasis area and severity index (PASI) directly correlate with plasma/serum Hcy levels [10,15,17,18].…”
Section: Hcy Levels In Patients With Psoriasismentioning
confidence: 99%
“…Mean PASI score was 9.16±3.91, ranging from 2.10 to 15.2. ere is no evidence of direct correlation between current disease severity and serum homocysteine levels O A Psoriasis is considered to be an independent risk factor for cardiovascular morbidity and mortality, but the exact underlying mechanisms have not yet been uncovered [3][4][5] . Some recent studies suggested that elevated serum homocysteine levels in psoriatic patients might contribute to the cardiovascular risk in psoriatic patients, due to their atherogenic and prothrombotic e ect [11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is sulfur containing amino acid, displaying atherogenic and prothrombotic features. It is produced in the metabolism of the essential amino acid methionine and can be catabolized by re-methylation to methionine in the presence of co-factors folic acid and vitamin B12 or by trans-sulfuration to cysteine in the presence of cofactor vitamin B6 8,[11][12][13][14][15] . Moreover, homocysteine promotes endothelial dysfunction and, consequently, atherosclerosis by reducing the bioavailability of nitric oxide due to inhibition of nitric oxide synthase (eNOS) and oxidative stress, provokes endothelial cell damage, and leads to a state of chronic in ammation of the endothelium 12,16 .…”
mentioning
confidence: 99%
“…Other studies have suggested that hyperhomocysteinaemia might account for the increased susceptibility to CVD in patients with psoriasis (5) . Furthermore, cardiovascular risk factors, such as dyslipidaemia, hypertension, oxidative stress, diabetes mellitus and metabolic syndrome are more prevalent among patients with psoriasis (6) .…”
Section: Introductionmentioning
confidence: 99%